Approach to Weighting the Success Criteria of Toll Road Project of Government Cooperation with Business Entities Procurement Model - Hidayat, Iman; Suhana, Asep; Padriani, Hetty (Newinera Publisher, 2024)
In providing funding for toll road development projects, many developing countries are im-plementing PPP pro-curement schemes including Indonesia. This funding scheme is believed to be an innovative procurement process model and has good prospects for the future of the construc-tion industry in the world. However, in its implementation, the Indonesian government is currently faced with various problems that have the potential to have a negative impact on the management and development of toll roads in Indo-nesia. Therefore, the main objective of this research is to develop a method of evaluating the success of PPP-themed toll road projects and determining the current and future strategy of PPP-themed toll road development projects. Methodology This research, using an exploratory sequential mixed methods approach, involves four stages of research. Through a Systematic Literature Review (SLR) of reputable scientific journals from various countries, a questionnaire survey was developed. The survey results were analyzed using multivariate statistical methods with the help of Par-tial Least square analysis software (PLS-SEM), analytical hierarchy process (AHP) and Relative Importance Index (RII) methods. The results of this research found 20 critical success indicators and four dimensions of project success. This study produces a new way to assess the success of PPP-themed toll road projects that is very important and can inspire the government in making policies, legislation and regulations as well as innovative strategies in develop-ing PPP-themed toll roads.